2021
DOI: 10.1016/j.jamda.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Post-Acute Care Utilization During the COVID-19 Pandemic

Abstract: Objective To examine the effect of the COVID-19 pandemic on post-acute care utilization and spending. Design We used a large national multi-payer claims dataset from January 2019 through October 2020 to examine trends in post-hospital-discharge location and spending Setting and participants We identified and included 975,179 hospital discharges who were 65 years or older. Methods We summarized post-discharge utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 9 publications
0
43
0
Order By: Relevance
“…In the absence of specific and validated instruments for evaluating perceived changes in home visit utilization and possible reasons during the COVID-19 pandemic, we developed an original questionnaire based on previous studies and discussion among the authors of the present study [ 5 , 9 11 ]. We confirmed the content validity by three physicians, and face validity of the questionnaires by three psychiatrists and one social worker.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of specific and validated instruments for evaluating perceived changes in home visit utilization and possible reasons during the COVID-19 pandemic, we developed an original questionnaire based on previous studies and discussion among the authors of the present study [ 5 , 9 11 ]. We confirmed the content validity by three physicians, and face validity of the questionnaires by three psychiatrists and one social worker.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies revealed changes in health care utilization in the outpatient clinic, hospital setting, and home care service due to the COVID-19 pandemic [ 4 , 5 , 9 11 ]. Xu et al reported significant reductions in inpatients, emergency department, and outpatient utilization in the early days of the pandemic [ 5 ]; however, other studies reported that the evidence in the home care setting in the USA was controversial [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As discretionary inpatient procedures paused and as nursing homes especially became a setting of last resort, new admissions were most likely individuals for whom staying at home was no longer safe. 9 , 10 Future research should incorporate clinical and functional assessment data and investigate the role of the facility and geographic factors to examine these trends in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…In England, the pandemic was initially considered as a short-term shock to demand in the care homes market, with occupancy levels expected to return to pre-pandemic levels (National Audit Office, 2020). Nonetheless, it is also likely that the impact of the pandemic will have accelerated changes in LTC systems (Werner and Bressman, 2021). The findings in this work indicate that an increase in supply of one main form of LTC need not come at the cost of a reduction in the other.…”
Section: Discussionmentioning
confidence: 99%